13CO2 breath test to measure the hydrolysis of various starch formulations in healthy subjects. Issue 2 (February 1990) - Hiele, M; Ghoos, Y; Rutgeerts, P; Vantrappen, G; de Buyser, K
Abstract : 13CO2 starch breath test was used to study the effect of physicochemical characteristics of starch digestion. As starch is hydrolysed to glucose, which is subsequently oxidised to CO2, differences in 13CO2 excretion after ingestion of different starch products must be caused by differences in hydrolysis rate. To study the effect of the degree of chain branching, waxy starch, containing 98% amylopectin, was compared with high amylose starch, containing 30% amylopectin, and normal crystalline starch, containing 74% amylopectin. The effect of the extent of gelatinisation was studied by comparing extruded starch and crystalline starch. Finally, the possible inhibitory effect of adding wheat fibre to extruded starch on the hydrolysis rate was studied. The 13CO2 excretion from two to four hours after intake of crystalline starch was significantly lower than that of extruded starch. Waxy starch was hydrolysed much faster than high amylose starch, but there was no significant difference between waxy starch and normal crystalline starch. Addition of wheat fibre did not influence the hydrolysis rate. The 13CO2 starch breath test is an attractive test for the study of factors affecting carbohydrate assimilation.